Aberrant DNA methylation of cancer-related genes in giant breast fibroadenoma: A case report - Marzese, Diego Matías (2016)
Introduction. Giant fibroadenoma is an uncommon variant of benign breast lesions. Aberrant methylation of CpG islands in promoter regions is known to be involved in the silencing of genes (for example, tumor-suppressor genes) and appears to be an early event in the etiology of breast carcinogenesis. Only hypermethylation of p16INK4a has been reported in non-giant breast fibroadenoma. In this particular case, there are no previously published data on epigenetic alterations in giant fibroadenomas. Our previous results, based on the analysis of 49 cancer-related CpG islands have confirmed that the aberrant methylation is specific to malignant breast tumors and that it is completely absent in normal breast tissue and breast fibroadenomas. Case presentation. A 13-year-old Hispanic girl was referred after she had noted a progressive development of a mass in her left breast. On physical examination, a 10 × 10 cm lump was detected and axillary lymph nodes were not enlarged. After surgical removal the lump was diagnosed as a giant fibroadenoma. Because of the high growth rate of this benign tumor, we decided to analyze the methylation status of 49 CpG islands related to cell growth control. We have identified the methylation of five cancer-related CpG islands in the giant fibroadenoma tissue: ESR1, MGMT, WT-1, BRCA2 and CD44. Conclusion: In this case report we show for the first time the methylation analysis of a giant fibroadenoma. The detection of methylation of these five cancer-related regions indicates substantial epigenomic differences with non-giant fibroadenomas. Epigenetic alterations could explain the higher growth rate of this tumor. Our data contribute to the growing knowledge of aberrant methylation in breast diseases. In this particular case, there exist no previous data regarding the role of methylation in giant fibroadenomas, considered by definition as a benign breast lesion.